2019
DOI: 10.1542/peds.2019-1509
|View full text |Cite
|
Sign up to set email alerts
|

Kingella kingae and Osteoarticular Infections

Abstract: OBJECTIVES: In this study, we aimed to contrast the bacteriologic epidemiology of osteoarticular infections (OAIs) between 2 patient groups in successive 10-year periods, before and after the extensive use of nucleic acid amplification assays in the diagnostic process. METHODS: Epidemiologic data and bacteriologic etiologies of all children presenting with OAIs on admission to our institution over 20 years (1997-2016) were assessed retrospectively. The population was divided into 2 cohorts, using the standardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(82 citation statements)
references
References 48 publications
3
77
0
Order By: Relevance
“…After admission, apyrexy was achieved on day 2.4 ± 1 [1][2][3][4]. Resolution of local signs of inflammation and impaired function were seen on day 7.1 ± 2.3 [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After admission, apyrexy was achieved on day 2.4 ± 1 [1][2][3][4]. Resolution of local signs of inflammation and impaired function were seen on day 7.1 ± 2.3 [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…3 Kingella kingae (K. kingae) plays a major role in children under four years old. 3,5,9 In a recent systematic review, Maria Wong et al 10 found a 30.8% prevalence of K. kingae osteoarticular infections in the paediatric population, with a significant increase under 48 months of age (47.6%). 10 Considering children with hemoglobinopathies SS or SC and those in developing countries, Salmonella species are an important cause of AO.…”
Section: Introductionmentioning
confidence: 99%
“…In the second group, where the molecular technique was used extensively, Kingella kingae was the most frequently isolated pathogen (51% of the confirmed cases) with an increase especially in children aged 6 to 48 months. Of note, the molecular technique overall improved the detection of the bacteria responsible for the infection, with 78.4% of identified cases compared to 59.4% during the first conventional period [7]. Pseudomonas aeruginosa and Streptococcus pyogenes could be responsible for infection after a trauma or surgery, while Salmonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on long-term outcomes of OM and SA mostly referred to pre-millennial patient cohorts. During the last two decades, management of osteoarticular infections in children has advanced with increasing use of magnetic resonance imaging (MRI), microbial testing (i.e., nucleic acid amplification and resistance testing) and recommendations for shorter treatment duration (17)(18)(19)(20)(21)(22)(23). Clearly, long-term outcome studies evaluating modern management are needed.…”
Section: Introductionmentioning
confidence: 99%